Effects of plant regulators and potassium nitrate, on Rangpur lime seeds germination - Leonel, S.; Rodrigues, J. D. (Inst Tecnologia Parana, 1995)
The effects of plant regulators and potassium nitrate were studied on 'Rangpur' lime (Citrus limonia Osbeck) seeds germination. The seeds were removed from ripe fruits, washed, dried and stored at 4 - 5 degrees C, and treated for 24 hours before sowing and the treatments were: KNO3 0,1% and 0,2%; GA(3) 50 ppm, 100 ppm and 250 ppm; GA(4+7)+phenylmethylaminepurine 100 ppm; phenylmethylaminepurine 20 ppm and control. The germination was evaluated begining 13 days after sowing. Best results were obtained with KNO3 0,2%, which proved most beneficial in enhancing percentage and germination rate.
Keywords: gibberellin; cytokinin; Citrus limonia